SEVERE ACUTE RESPIRATORY SYNDROME CORONAVIRUS 2 (SARS-CoV-2) VACCINE-INDUCED THYROID DYSFUNCTION: A TALE OF TWO PATIENTS - Ng, Siew Mei; Affendi, Sharifah Noor Adrilla Binti Long Mohd Noor; Chai, Shu Teng (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION SARS-CoV-2 vaccine has been the main pillar in battling the coronavirus disease 2019 (COVID-19) pandemic. However, the current vast scale of SARS-CoV-2 vaccination programme has led to inevitable reports of various adverse reactions, one of which include thyroid dysfunction. CASES We describe two patients who manifested hyperthyroidism following BNT162b2 mRNA-based COVID-19 vaccine boosters. Patient 1, a previously euthyroid 46-year-old female, has an eight-year history of type 1 diabetes mellitus. She developed palpitations of increasing severity about two weeks after her COVID-19 booster vaccine on 20th January 2022. She had weight loss of 4 kg and experienced menstrual irregularities in the subsequent three months. Examination revealed tachycardia (112 beats per minute, regular) and bilateral fine tremors of the hands. There was no goitre or neck tenderness. Blood investigations showed overt hyperthyroidism with positive thyroid autoantibodies, consistent with Graves’ disease. Treatment with carbimazole led to marked symptomatic improvement. Patient 2, a 38-year-old female with a six-year history of Hashimoto thyroiditis, was clinically and biochemically euthyroid while taking levothyroxine 100 mcg daily prior to her COVID-19 booster vaccine on 5th January 2022. Five weeks following the vaccine, her thyroid function test during her endocrine clinic appointment showed overt hyperthyroidism, which was confirmed by a second blood sample ten days later. There was neither a change in levothyroxine dose nor any additional supplement intake. She was otherwise asymptomatic. Levothyroxine was then withheld. She regained her baseline hypothyroid state two weeks later, during which levothyroxine was resumed. CONCLUSION SARS-CoV-2 vaccine-induced thyroid dysfunction can affect both euthyroid and hypothyroid patients. A history of recent COVID-19 vaccination should be included in the clinical evaluation of a newly diagnosed hyperthyroid patient or unexplained hyperthyroidism in a long-standing hypothyroid patient.